2003
DOI: 10.1113/jphysiol.2002.029132
|View full text |Cite
|
Sign up to set email alerts
|

Reduced contraction strength with increased intracellular [Ca2+] in left ventricular trabeculae from failing rat hearts

Abstract: Intracellular calcium ([Ca2+]i) and isometric force were measured in left ventricular (LV) trabeculae from spontaneously hypertensive rats (SHR) with failing hearts and normotensive Wistar‐Kyoto (WKY) controls. At a physiological stimulation frequency (5 Hz), and at 37 °C, the peak stress of SHR trabeculae was significantly (P≤; 0.05) reduced compared to WKY (8 ± 1 mN mm−2(n= 8)vs. 21 ± 5 mN mm−2(n= 8), respectively). No differences between strains in either the time‐to‐peak stress, or the time from peak to 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 60 publications
(77 reference statements)
5
55
0
Order By: Relevance
“…Peak ϪdP LV /dt is the maximum rate of fall in LV pressure during the cardiac cycle and a measure of diastolic dysfunction (31). Decreased ϪdP LV /dt reflects increased stiffness of the LV wall, which may be associated with increased content (32,33) and altered three-dimensional organization (33) of fibrous connective tissue structures such as those formed by collagen. Maximum ϪdP LV /dt was impaired in diabetic hearts compared with controls ( Fig.…”
Section: Figmentioning
confidence: 99%
“…Peak ϪdP LV /dt is the maximum rate of fall in LV pressure during the cardiac cycle and a measure of diastolic dysfunction (31). Decreased ϪdP LV /dt reflects increased stiffness of the LV wall, which may be associated with increased content (32,33) and altered three-dimensional organization (33) of fibrous connective tissue structures such as those formed by collagen. Maximum ϪdP LV /dt was impaired in diabetic hearts compared with controls ( Fig.…”
Section: Figmentioning
confidence: 99%
“…The [Ca 2ϩ ] e range was designed to include a nominally zero level of Ca 2ϩ , the typical Ca 2ϩ level in a resting myocyte (100 nM), and the Ca 2ϩ level averaged over a beat (350 nM) in a myocyte stimulated at heart rates achievable in the intact animal (7,8). The measurements of Dibb et al (7) showed an average Ca 2ϩ concentration of 361.5 nM at 6 Hz in isolated myocytes (control group), and those of Ward et al (8) showed an average Ca 2ϩ concentration of 300 nM at 5 Hz in isolated trabeculae. Experiments were also performed at [Ca 2ϩ ] e Ͼ 750 nM with limiting pyruvate/malate.…”
Section: Control Of Extramitochondrial Free Buffer Ca 2ϩ Concentratiomentioning
confidence: 99%
“…Previous studies (4, 6) have been restricted to substrates that provided the maximal calcium effect. The major point of this study was to examine the effect of calcium on mitochondrial respiration and NAD(P)H using pyruvate, which is the product of glycolysis entering the terminal oxidative pathway in mitochondria.Neither the respiration and NAD(P)H production rates nor the observed redox levels showed any apparent stimulatory effect of external Ca 2ϩ over an average concentration range observed in isolated trabeculae and cells at physiological temperature and stimulation frequencies (7,8). Over a range of substrate concentration and at high initial P i , only a 22-27% stimulatory effect on maximal State 3 respiration (which is never attained in vivo) was observed without a significant change in the corresponding NAD(P)H fraction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To do this, we used left ventricular (LV) tissue at 37°C and stimulation frequencies of 0.1-7 Hz. The latter encompasses rates used in other studies and the normal heart rate for rats in the absence of ␤-adrenergic stimulation (21). Because LV remodeling is also known to occur in diabetic cardiomyopathy (22,23), we examined extracellular matrix type I and III collagen (the most abundant collagen types in heart tissue [24]) and the thin contractile filament F-actin by immunohistochemistry and confocal microscopy and quantified their distribution and abundance.…”
mentioning
confidence: 99%